2001
DOI: 10.1111/j.1600-0463.2001.tb05802.x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic activity of estradiol and its metabolites in the ER‐CALUX assay with human T47D breast cells

Abstract: A number of metabolites of 17b-estradiol were tested for their estrogenic activity using the ER-CA-LUX assay based on the increased expression of luciferase in exposed T47D breast cancer cells. E 2 b and estrone showed similar potencies in the test, whereas E 2 a was 100 times less active. Incubation of cells with estrone (0.35 mM) resulted in the formation of E 2 b, whereas the reverse reaction was observed for E 2 b. The resulting equilibrium may explain the similar estrogenic potency of estrone in the test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 17 publications
3
20
0
1
Order By: Relevance
“…Our observations were consistent with the results of [15], who demonstrated that 4-OH-E2 is more oestrogenic than 2-OH-E2. In [16] it was indicated that certain oestradiol metabolites, i.e., 4-OH-E2 and 16-OH-E2, are able to mimic the effects of 17β-oestradiol on proliferation and markers of tumour metastasis.…”
Section: Action Of E2 and Its Hydroxylated Metabolites (2-oh-e2 And 4supporting
confidence: 83%
“…Our observations were consistent with the results of [15], who demonstrated that 4-OH-E2 is more oestrogenic than 2-OH-E2. In [16] it was indicated that certain oestradiol metabolites, i.e., 4-OH-E2 and 16-OH-E2, are able to mimic the effects of 17β-oestradiol on proliferation and markers of tumour metastasis.…”
Section: Action Of E2 and Its Hydroxylated Metabolites (2-oh-e2 And 4supporting
confidence: 83%
“…Differences in metabolism were often responsible for the differences found between different cell lines and between cell lines and yeast-based bioassays [36,46,47]. Estrone for instance showed a REP of 0.2 in a proliferation test based on human breast cancer cells (Escreen) and the yeast estrogen bioassay, but was equally potent to E2 in a transcription activation assay based on human T47-D breast cancer cells [16,21,46]. In the ER-CALUX test with the T47-D breast cancer cells, the 17β-hydroxysteroid dehydrogenase 3 enzyme was responsible for the conversion of estrone into E2 and vice versa [46].…”
Section: Discussionmentioning
confidence: 99%
“…[154][155][156][157][158] The prime motivation for studying these compounds was to search for potent STS inhibitors lacking the estrogenic effect displayed by EMATE based on the knowledge that 2-methoxyestradiol, an endogenous mammalian metabolite of estradiol, and 2-methoxyestrone are substantially less estrogenic than estrone and estradiol. 159,160 Indeed, the 2-methoxy analog 17a is a potent inhibitor of STS and shows tumor regression but no estrogenic effect in vivo. 65,154 With regard to STS inhibitory potency, 2-methoxy EMATE was approximately 7.5 times less active than EMATE as assessed in placental microsomes.…”
Section: Steroidal Arylsulfamatesmentioning
confidence: 99%